Open Tibial Fracture in a Non-Compliant Patient: A Case Report - Samuele Pizzolo; Gianluca Testa; Giacomo Papotto; Giuseppe Mobilia; Giovanni Di Stefano; Giuseppe Sessa; Vito Pavone (Journal of Functional Morphology and Kinesiology, 2018)
Open tibial fractures represent the most frequent fractures of long bones, comprising approximately 1.9% of all fractures. Although locked intramedullary nailing is the gold standard for treating closed and unstable tibia diaphyseal fractures, for most exposed fractures, an external fixator can first be used, followed by conversion through an intramedullary nail. The present report describes the case of a 17-year-old male who presented with a complex multi-segmented displaced tibia fracture, type 42-C3, with exposure of IIIB type according to the Gustilo–Anderson classification, and with an attached disrupted fracture of peroneal malleolus, type 44-B2. External fixation was the preferred treatment method. Before the definitive surgical treatment, the patient had a second accident that caused refracture and damage to the soft tissues and external fixation system. This prolonged the time estimated for the conversion from the external fixator to the intramedullary nail. The reported case shows the use of various treatment steps with different timelines and an intervention with vacuum-assisted closure therapy for soft tissue healing as well as subsequent intramedullary nailing in order to reach the definitive healing of a non-compliant patient. These combined methods achieved an acceptable reduction and good stability of such a complex fracture.